2021
DOI: 10.1002/jctb.6839
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and partial characterization of Komagataeibacter sp. SU12 and optimization of bacterial cellulose production using Mangifera indica extracts

Abstract: BACKGROUND Recycling food wastes into high‐value‐added products not only impacts beneficially on the environment but also on local economies. Mango wastes represent more than 92 000 tons per year in Peru. Bioconversion of mango waste into bacterial cellulose (BC) can provide valuable products in biomedicine. RESULTS Screening of BC producers in kombucha tea allows the selection of wild‐type strains. One of the selected wild‐type strains, named SU12, was cultured in batch using Hestrin–Schramm (HS) synthetic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…For example, Bagewadi et al [18] used Plackett-Burmann's design to optimize the culture medium for producing BC by Enterobacter hormaechei. In another study, Calderón-Toledo et al [19] supplemented HS medium with mango extracts and optimized BC production by Komagataeibacter sp. SU12 using Plackett-Burmann's design and compared the purified BCs produced by standard and mango-modified media.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bagewadi et al [18] used Plackett-Burmann's design to optimize the culture medium for producing BC by Enterobacter hormaechei. In another study, Calderón-Toledo et al [19] supplemented HS medium with mango extracts and optimized BC production by Komagataeibacter sp. SU12 using Plackett-Burmann's design and compared the purified BCs produced by standard and mango-modified media.…”
Section: Introductionmentioning
confidence: 99%
“…In these works, the focus was in the selection and optimization of the biocatalyst, bioreactor configuration, or the experimental conditions. Calderón‐Toledo et al 13 . reported the bioconversion of mango wastes into cellulose by wild‐type bacterial strains, which has applications in food, cosmetic and medicine industries.…”
mentioning
confidence: 99%
“…In these works, the focus was in the selection and optimization of the biocatalyst, bioreactor configuration, or the experimental conditions. Calderón-Toledo et al 13 reported the bioconversion of mango wastes into cellulose by wild-type bacterial strains, which has applications in food, cosmetic and medicine industries. Amaya-Chantaca et al 14 showed the potential of pomace from the winemaking industry as a fermentation substrate for the extraction of phenolic compounds in submerged and solid-state fermentation using Aspergillus niger GH1 as a biological model.…”
mentioning
confidence: 99%